A qPCR assay for the detection of Phytophthora abietivora, an emerging pathogen on fir species cultivated as Christmas trees. - Guillaume Charron; Marie-Krystel Gauthier; Hervé van der Heyden; Guillaume J Bilodeau; Philippe Tanguay (PLoS ONE)
Emerging species of the Phytophthora genus are among the most important threats to global plant biodiversity, horticulture and trade. For instance, Phytophthora root rot (PRR) of Christmas trees, mainly Fraser (Abies fraseri) and balsam (Abies balsamea) firs, is responsible for an average of 10% of the observed diseased trees in plantations. Diagnosing PRR involves isolation followed by morphological and molecular identification of the causal agents. However, these methods are rarely adapted to larger scale monitoring such as in situ detection. For these applications, molecular detection of environmental DNA (eDNA) provides the fast and high-throughput results needed. Phytophthora abietivora was associated with PRR in firs (Abies spp.) cultivated as Christmas trees in the province of Québec (Canada). This study focused on developing a sensitive and specific qPCR assay targeting P. abietivora and validating its efficiency on DNA extracted from soil and roots. A set of primers and probe was designed for this assay, and parameters such as the limit of detection (LOD95%) and limit of quantification (LOQ) were measured. The assay was tested on DNA obtained from healthy-looking and PRR symptomatic Fraser and balsam firs. The assay was shown to be semi-specific because it cross-reacted with P. europaea and three other phylogenetically close species, but deemed specific in the context of PRR of firs. The LOD95% was estimated at 10 copies per reaction (Cq of 35.7) and the LOQ to 33 P. abietivora oospores per gram of soil. Out of 488 DNA samples from soil, 68 were positive for P. abietivora from which 42 (61.7%) were from PRR symptomatic trees. Only a slight overlap (3 out of 7 samples) was observed with previously obtained baiting results. This assay will be useful for rapid diagnostics of P. abietivora infected trees and as a prospecting tool to better characterize the natural distribution and dissemination of the disease.